Fatigue, anxiety, depression and quality of life in kidney transplant recipients, haemodialysis patients, patients with a haematological malignancy and healthy controls - van Sandwijk, Marit S; Al Arashi, Doaa; van de Hare, Fons M; van der Torren, J M Rolien; Kersten, Marie-José; Bijlsma, Joost A; Ten Berge, Ineke J M; Bemelman, Frederike J (Nephrology, dialysis, transplantation, 2019)
The impact of haemodialysis (HD) and kidney transplantation on quality of life (QoL) is often underestimated due to a lack of comparative studies with other patient groups. We conducted a cross-sectional cohort study in 168 patients including HD patients, kidney transplant recipients (KTR), patients with a haematological malignancy either receiving chemotherapy or in remission and healthy controls. All participants completed the 36-item short form survey of health-related quality of life, the Checklist Individual Strength and the Hospital Anxiety and Depression Scale questionnaire. HD patients and haematological patients undergoing chemotherapy were more frequently severely fatigued (53.3% and 50% of cases) compared with KTR (33.3%), haematological patients in remission (23.3%) and healthy controls (12.1%, P < 0.001). There were no significant differences in anxiety rates. HD patients and haematological patients undergoing chemotherapy were most likely to be depressed (33.3% and 25%), compared with 16.7% of KTR, 20% of haematological patients in remission and 8.6% of healthy controls (P = 0.066). KTR reported the largest positive health change (+27%, P < 0.001), but still had a lower overall QoL than healthy controls, comparable to haematological patients in remission. HD and chemotherapy patients reported the lowest QoL scores. Fatigue and depression are common in HD patients, resulting in a low QoL, comparable to haematological patients receiving chemotherapy. KTR do better, with scores similar to patients with a haematological malignancy in remission, but still have a lower QoL than healthy controls.